Two-Photon Resonant Third Harmonic Generation IN Hg. Issue 2 (1993) - Koudoumas, E.; Efthimiopoulos, T.
Abstract : Third-harmonic generation in Hg vapors, using the two-photon resonance 6 1 S0 –8 1 S0 transition is theoretically and experimentally investigated. Calculations of the Hg contribution to the phase mismatch are presented and the effects of the absorption of the radiation, the population transfer, the saturation, and the ionization on the efficiency of the system are considered. It is shown that the population transfer is the dominant mechanism affecting the efficiency.